THE IMPACT OF THE INTRODUCTION OF ARTIFICIAL INTELLIGENCE ON THE LABOR MARKET USING THE METHOD OF PHASE PORTRAITS - MISIURKA, PAVLO (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article presents the results of a detailed analysis of current models and system solutions regarding the impact of the introduction of artificial intelligence (AI) on the labor market. The conducted research covers a wide range of issues related to the transformation of the labor market under the influence of the latest technologies. It is considered how automation and the use of AI change the demand for various professions, affect the structure of employment, create new jobs, and at the same time leads to the disappearance of traditional professions.A new information technology for modeling the impact of AI on the labor market is proposed, which is based on the method of phase portraits. This technology allows you to visualize and predict the dynamics of changes in the labor market due to the introduction of AI. The method of phase portraits provides an opportunity not only to analyze the current state of the market, but also to predict future trends, which is critically important for the development of strategies for adaptation to new conditions.The article identifies key aspects affecting the level of employment, the labor market structure, and changing requirements for workers and their skills. Emphasis is placed on the growing need for specialists with knowledge in the field of information technology, data analysis and management of AI systems. The information technology for modeling the impact of artificial intelligence on the formation of the labor market using phase portraits, determining the key aspects of the employment level, the structure of the labor market, as well as the change in requirements for employees and their skills, and analyzing the work of the model is proposed.
Keywords: artificial intelligence; aspects of employment level; method of phase portraits; labor market dynamics; technological changes; forecasting